The role of recombination in telomere length maintenance. (20th May 2009) - Royle, Nicola J.; Méndez-Bermúdez, Aarón; Gravani, Athanasia; Novo, Clara; Foxon, Jenny; Williams, Jonathan; Cotton, Victoria; Hidalgo, Alberto
Abstract : Human telomeres shorten during each cell division, predominantly because of incomplete DNA replication. This eventually results in short uncapped telomeres that elicit a DNA-damage response, leading to cellular senescence. However, evasion of senescence results in continued cell division and telomere erosion ultimately results in genome instability. In the long term, this genome instability is not sustainable, and cancer cells activate a TMM (telomere maintenance mechanism), either expression of telomerase or activation of the ALT (alternative lengthening of telomeres) pathway. Activation of the ALT mechanism results in deregulation of recombination-based activities at telomeres. Thus ALT+ cells show elevated T-SCE (telomere sister-chromatid exchange), misprocessing of t-loops that cap chromosomes and recombination-based processes between telomeres or between telomeres and ECTRs (extrachromosomal telomeric repeats). Some or all of these processes underlie the chaotic telomere length maintenance that allows cells in ALT+ tumours unlimited replicative capacity. ALT activation is also associated with destabilization of a minisatellite, MS32. The connection between the minisatellite instability and the deregulation of recombination-based activity at telomeres is not understood, but analysis of the minisatellite can be used as a marker for ALT. It is known that telomere length maintenance in ALT+ cells is dependent on the MRN [MRE11 (meiotic recombination 11)–Rad50–NBS1 (Nijmegen breakage syndrome 1)] complex, but knowledge of the role of other genes, including the Werner's ( WRN ) and Bloom's ( BLM ) syndrome DNA helicase genes, is still limited.